Development of natural fibre based flexural composite: A sustainable mimic of natural leather. (August 2022) - Basak, S.; Shakyawar, D.B.; Samanta, Kartick K.; Debnath, Sanjoy; Bhowmick, M.; Kumar, Niranjan
Abstract: A natural fibre based flexural composite has been developed by using suitable chemical formulation of natural rubber, sulphur dispersion, accelerator, activator, stabilizer, filler antioxidant etc. with needle punched ramie non-woven fabric. Developed natural fibre based flexural composite products have been examined in terms of different physical properties like absorbency, wicking, swelling, shrinkage. The performance properties i.e abrasion resistance, tensile strength, tear strength, puncture resistance, permeability, porosity and dynamic loading and recovery of the developed product has also been examined and compared with the wet blue (chrome treated) leather of goat. Absorbency time and rate of vertical wicking of the wet blue leather are almost equal as compared to the developed flexural composite whereas composite product shows 20 % higher permeability and less shrinkage as compared to the natural leather. Tensile strength of the developed product was 50 % less whereas tear strength is almost equal as compared to the natural leather, having same weight and thickness. Surface and cross-sectional morphology of the flexural composite and natural leather has also been characterized by scanning electron microscopy analysis. The thermo-gravimetry (TG), atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR) analysis of developed composites have also characterized. and compare with the natural leather. Graphical abstract: ga1